Making a lot with little – Modular architecture, starting with Walter Segal - Niccolò Di Virgilio (Agathón)
This paper examines the remarkable design journey of the Jewish architect Walter Segal and his fifty-year career in London. After his early experiments in Ascona (Switzerland), Segal developed a system of construction in wood that was based on using the modular components of materials in the forms that were available on the market. This method attracted considerable interest, being both simple and economical, and went on to become a system of self-build construction. The paper attempts to follow some of the hidden channels that link Segal’s practice with movements within the complex geography of contemporary architectural design: movements that focus on reclaiming ‘making’, on the sustainability intrinsic in Segal’s principles, and on a pragmatic aesthetic that takes account of events and external circumstances to achieve ‘more’ with ‘less’.